Homo-trimeric Structure of the Type IVb Minor Pilin CofB Suggests Mechanism of CFA/III Pilus Assembly in Human Enterotoxigenic Escherichia coli. Issue 6 (27th March 2016) - Kawahara, Kazuki; Oki, Hiroya; Fukakusa, Shunsuke; Yoshida, Takuya; Imai, Tomoya; Maruno, Takahiro; Kobayashi, Yuji; Motooka, Daisuke; Iida, Tetsuya; Ohkubo, Tadayasu; Nakamura, Shota
Abstract: In gram-negative bacteria, the assembly of type IV pilus (T4P) and the evolutionally related pseudopilus of type II secretion system involves specialized structural proteins called pilins and pseudopilins, respectively, and is dynamically regulated to promote bacterial pathogenesis. Previous studies have suggested that a structural "tip"-like hetero-complex formed through the interaction of at least three minor (pseudo) pilins plays an important role in this process, while some members of the pathogenic type IVb subfamily are known to have only one such minor pilin subunit whose function is still unknown. Here, we determined the crystal structure of the type IVb minor pilin CofB of colonization factor antigen/III from human enterotoxigenic Escherichia coli at 1.88-Å resolution. The crystal structure, in conjunction with physicochemical analysis in solution, reveals a symmetrical homo-trimeric arrangement distinct from the hetero-complexes of minor (pseudo) pilins observed in other T4P and type II secretion systems. Each CofB monomer adopts a unique three-domain architecture, in which the C-terminal β -sheet-rich lectin domain can effectively initiate trimer association of its pilin-like N-terminal domain through extensive hydrophobic interactions followed by domain swapping at the central hinge-like domain. Deletion of cofB produces a phenotype with no detectable pili formation on the cell surface, while molecular modeling indicates that the characteristic homo-trimeric structure of CofB is well situated at the pilus tip of colonization factor antigen/III formed by the major pilin CofA, suggesting a role for the minor pilin in the efficient initiation of T4P assembly. Graphical abstract: Highlights: In gram-negative bacteria, the question of how pilins are assembled to form a type IV pilus remains unknown. The type IV pilin CofB solely identified as a minor pilin in the colonization factor antigen/III pilus system promotes type IV pilus assembly. The CofB takes a homo-trimetric, tip-like structure, which is well situated at the top of the CFA/III pilus. This study enhances our understanding of the mechanism of filament assembly in type II secretion and type IV pilus systems.